Novel Approaches to Understanding and Conceptualizing Diaspora - Pataki, Éva (Hungarian Journal of English and American Studies, 2020)
Book review: Ilott, Sarah, Ana Cristina Mendes, and Lucinda Newns, eds. New Directions in Diaspora Studies: Cultural and Literary Approaches. London, New York: Rowman and Littlefield, 2018. xxxiii + 165 pages. ISBN 978-1-78660-516-0. Hb. £85.